Racial/Ethnic Disparities in Quality of Care for Cardiovascular Disease in Ambulatory Settings: A Review. (June 2018) - Dong, Liming; Fakeye, Oludolapo A.; Graham, Garth; Gaskin, Darrell J.
Racial and ethnic disparities in cardiovascular disease (CVD) outcomes are widely reported, but research has largely focused on differences in quality of inpatient and urgent care to explain these disparate outcomes. The objective of this review is to synthesize recent evidence on racial and ethnic disparities in management of CVD in the ambulatory setting. Database searches yielded 550 articles of which 25 studies met the inclusion criteria. Reviewed studies were categorized into non-interventional studies examining the association between race and receipt of ambulatory CVD services with observational designs, and interventional studies evaluating specific clinical courses of action intended to ameliorate disparities. Based on the Donabedian framework, this review demonstrates that significant racial/ethnic disparities persist in process and outcome measures of quality of ambulatory CVD care. Multimodal interventions were most effective in reducing disparities in CVD outcomes.